2013
DOI: 10.1371/journal.pone.0068244
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Legionella and Free-Living Amoebae in Composts and Bioaerosols from Composting Facilities

Abstract: Several species of Legionella cause Legionnaires’ disease (LD). Infection may occur through inhalation of Legionella or amoebal vesicles. The reservoirs of Legionella are water, soil, potting soil and compost. Some species of free-living amoebae (FLA) that are naturally present in water and soil were described as hosts for Legionella. This study aimed to understand whether or not the composting facilities could be sources of community-acquired Legionella infections after development of bioaerosols containing L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 32 publications
2
37
0
1
Order By: Relevance
“…); sediment from a rice field in Vercelli Italy (Murase and Frenzel ); and soil from composting facilities in southern Switzerland (Conza et al. ). A more detailed review of these kinds of findings can be found elsewhere (Geisen et al.…”
mentioning
confidence: 99%
“…); sediment from a rice field in Vercelli Italy (Murase and Frenzel ); and soil from composting facilities in southern Switzerland (Conza et al. ). A more detailed review of these kinds of findings can be found elsewhere (Geisen et al.…”
mentioning
confidence: 99%
“…A closer look to individual filter identifications showed a large variability in the number of proteins identified for each filter. In particular, for the CP filters (Tables S2 and S4, Supporting Information) variations were due to bioaerosol emission rates and dispersion influenced by many factors, including compost temperature, sorting, shredding and turning of the piles, meteorological conditions (e.g., temperature, humidity, wind, and weather), and the composition of the source organic material . Few proteins were identified from the two filters from the WWTP (only 15 proteins and 17 peptides); such small numbers were probably due to the fact that aerosol components, such as carbonaceous material, may hamper protein sample preparation.…”
Section: Resultsmentioning
confidence: 99%
“…Finally this is also a good opportunity to test the storage, enumeration and identification procedure, be that through cultivation and visual enumeration of the cfu, various PCR techniques, metagenomics, mass spectrometry, epifluorescence microscopy, matrix-assisted laser desorption/ionization mass spectrometry or other means. 3,21,23,50,54,60,92,93 These enumeration and identification methods, along with their advantages and limitations, have recently been discussed and are not repeated here; however, it should be noted that quantification of the pathogens captured by active samplers is normally expressed per cubic metre of air, which provides another reason to determine accurately the air flow rate of the device and the sampling time-period. 11,50,53,92 Bioaerosol sampling out in the field The statistical analysis relating to bioaerosol sampling varies considerably depending on the nature of the study, and an investigator would do well to consult a statistician when designing any study.…”
Section: Air Streamlinesmentioning
confidence: 99%
“…3,21,23,50,54,60,92,93 These enumeration and identification methods, along with their advantages and limitations, have recently been discussed and are not repeated here; however, it should be noted that quantification of the pathogens captured by active samplers is normally expressed per cubic metre of air, which provides another reason to determine accurately the air flow rate of the device and the sampling time-period. 11,50,53,92 Bioaerosol sampling out in the field The statistical analysis relating to bioaerosol sampling varies considerably depending on the nature of the study, and an investigator would do well to consult a statistician when designing any study. 3,106,110 Errors arising from bioaerosol sampling are typically threefold: random error of samples containing a finite number of discrete particles; errors due to non-uniformity of the bioaerosol distribution in the atmosphere; and errors due to sampling techniques.…”
Section: Air Streamlinesmentioning
confidence: 99%